ANALISIS DAMPAK WORKING CAPITAL TURNOVER, STRUKTUR MODAL, ASSET GROWTH, DAN SALES GROWTH TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SUB SEKTOR ANEKA INDUSTRI OTOMOTIF DAN KOMPONENNYA YANG TERDAFTAR DI BEI TAHUN 2020-2024 - Shantika, Anggi Dwi; Parhusip, Austin Alexander (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
Company financial performance is a periodic evaluation of the operational effectiveness of an organization, institution, or employee in achieving predetermined goals, standards, and criteria. This study uses empirical data obtained from the Indonesia Stock Exchange (IDX) through the official website (https://www.idx.co.id) in the form of Financial Reports on various automotive and component sub-sector companies listed on the IDX for the period 2020-2024. The population used in this study is the population of the Various Automotive and Component Sub-Sector Companies for the period 2020-2024, totaling 20 companies, and 9 of them were sampled using the purposeful sampling method, so that the number of observations in this study was 45 observations. Based on the partial results, Working Capital Turnover and Sales Growth have a significant effect on financial performance, while Capital Structure and Asset Growth do not have a positive and significant effect on financial performance. While simultaneously, Working Capital Turnover, Capital Structure, Asset Growth, and Sales Growth have a significant effect on Financial Performance together.